1987
DOI: 10.1007/bf01020348
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic properties of cnicin, a sesquiterpene lactone fromcentaurea maculosa (spotted knapweed)

Abstract: Water and solvent extracts from the aerial tissues ofCentaurea maculosa, spotted knapweed, inhibited the root growth of lettuce. Column chromatography and lettuce bioassay of a chloroform extract led to the isolation of cnicin, a sesquiterpene lactone. Pure cnicin was bioassayed at 0, 1, 2, 4, 6, 8, and 10 mg/5 ml water with lettuce, created wheatgrass, bluebunch wheatgrass, rough fescue, western larch, lodgepole pine, and spotted knapweed. Germination was inhibited at one or more concentrations for all specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…The results showed an important production of sesquiterpene lactones, an important toxin with known activity against generalist herbivores (Amorim et al 2013), that gradually increased in C. solstitialis' non-native regions (Sotes et al 2015). Other preceding works with Centaurea invasive species had also suggested that sesquiterpene lactones could play a significant role in their success in their non-native regions (Kelsey & Locken 1987, Stevens et al 1990, Landau et al 1994. In order to experimentally assess for potential differences in SDH patterns we fed generalist herbivore Helix aspersa Müller, 1,774 snails with leaves from the invasive C. solstitialis, and also with leaves of the exotic but non-invasive C. sulphurea Lag.…”
Section: Introductionmentioning
confidence: 77%
“…The results showed an important production of sesquiterpene lactones, an important toxin with known activity against generalist herbivores (Amorim et al 2013), that gradually increased in C. solstitialis' non-native regions (Sotes et al 2015). Other preceding works with Centaurea invasive species had also suggested that sesquiterpene lactones could play a significant role in their success in their non-native regions (Kelsey & Locken 1987, Stevens et al 1990, Landau et al 1994. In order to experimentally assess for potential differences in SDH patterns we fed generalist herbivore Helix aspersa Müller, 1,774 snails with leaves from the invasive C. solstitialis, and also with leaves of the exotic but non-invasive C. sulphurea Lag.…”
Section: Introductionmentioning
confidence: 77%
“…No differences in herbivore damage between plants from different origins were detected in the French sites of the reciprocal transplant experiment, suggesting that invasive French plants maintained defence against generalists (but also that they were not better defended). Finally, sesquiterpene lactones that have phytotoxic properties (Kelsey and Locken 1987) are also involved in ragweed allelopathy (Be´res et al 1998). For all of these reasons reallocation of resources from at least this class of defences to growth and reproduction may not have been selected in A. artemisiifolia.…”
Section: Differences In Vigourmentioning
confidence: 99%
“…Examples of phytochemicals with multiple activities include cnicin in spotted knapweed (Kelsey & Locken 1987;Landau et al 1994), glucosinolates in the Brassicaceae (Siemens et al 2002) and monoterpenes in Thymus vulgaris (Linhart & Thompson 1999). If potent novel phytochemistry commonly manifests itself through multiple biological activities, leaf herbivory could be a useful proxy for allelopathy or antimicrobial activity in predicting invasiveness because it is simple to measure.…”
Section: Discussionmentioning
confidence: 99%